An affordable option to Au single crystals through cathodic corrosion of a wire: Fabrication, electrochemical behavior, and applications in electrocatalysis and spectroscopy. (10th March 2021) - Elnagar, Mohamed M.; Hermann, Johannes M.; Jacob, Timo; Kibler, Ludwig A.
Graphical abstract: Image, graphical abstract Abstract: Faceting and nanostructuring of polycrystalline gold electrodes by cathodic corrosion in concentrated potassium hydroxide electrolytes has been systematically studied at different electrode potentials. Current-potential curves for the restructured Au electrodes in 0.1 M H2 SO4 show characteristics of Au(111) in the double-layer and oxidation region. Thus, the modified Au electrodes adopt properties typically known for well-defined single crystal surfaces. Besides the preferential surface faceting, the electrochemically active surface area (EASA) is enhanced as a function of potential, concentration and time. Scanning electron micrographs show the formation of triangular pits and nanostructures with a specific orientation confirming the formation of (111)-facets. In this way, the behavior of single crystals is accompanied with the properties of nanoparticles which are of utmost interest in electrocatalysis and surface-enhanced Raman spectroscopy (SERS). The electrocatalytic activity of the newly formed "Au(111)" surface from an Au wire has been tested towards the hydrogen evolution reaction (HER) and for the formic acid oxidation reaction (FAOR). The study of electrocatalytic reactions at these nanostructured electrodes allows to identify active centers, which are absent for extended single crystal surfaces. Adsorbed pyridine on the nanostructured Au electrodes directly shows SERS activity, while untreated polycrystalline Au is SERS-inactive. The use of cathodic corrosion of simple wires is a paradigm of SERS-applications in electrochemistry with clean Au electrodes that provide properties of Au(111) single crystals.